Sustainable Green Material Applied in Architecture Building - Prasetya, Syahrian Ricky (Proceedings of International Conference of Graduate School on Sustainability, 2026)
In response to the growing urgency of environmental sustainability, this literature review explores the implementation of green building principles, sustainable architectural strategies, and the use of refurbished materials within the Indonesian architectural context. By synthesizing findings from recent academic journals and case studies, the paper identifies prevailing design approaches, evaluates the integration of passive and active environmental systems, and examines the socio-cultural and climatic considerations unique to Indonesia. The review also highlights the challenges of adopting sustainable practices, including regulatory limitations, cost constraints, and material availability, while uncovering opportunities for innovation through vernacular adaptation and circular design. This study aims to provide architects and design professionals with a comprehensive understanding of current trends and critical insights to inform future sustainable architectural practices in Indonesia. However, significant challenges remain, including limited comprehensive regulations, high initial investment costs, limited certified human resources, and a suboptimal supply chain for refurbished materials. Development opportunities lie in fiscal incentives, strengthening national standards, cross-sector collaboration, and integrating local wisdom and recycling technology innovation. Case studies and post-occupancy performance evaluations highlight the importance of ongoing monitoring and design adaptation to Indonesia’s tropical climate. The review recommends strengthening regulations, professional education, and further research related to life-cycle assessment and the development of sustainable local materials to support the green architecture agenda in Indonesia. These findings serve as a reference for architects in integrating sustainability principles, material innovation, and socio-cultural adaptation into current and future Indonesian architectural design practices.